NILAI, NORMA, MORAL, ETIKA DAN PANDANGAN HIDUP PERLU DIPAHAMI OLEH SETIAP WARGA NEGARA DALAM KEHIDUPAN BERBANGSA DAN BERNEGARA - ., Suyatno (PKn Progresif, 2012)
To realize a good citizen in the life of the nation it is necessary to understand the sense of values, norms, morals, ethics and view of life as this dakan any behavior or attitude underlying the actions of every citizen in achieving the goal of living together. And with an understanding of values, norms, morals, ethics, and philosophy of life is pervasive in every citizen, will strengthen the existence of the country's own citizens to live a life of nation and state.